2013
DOI: 10.1186/1756-0500-6-62
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal recovery after severe respiratory failure due to influenza: a case report

Abstract: BackgroundDuring pregnancy women are at increased risk of severe complications to influenza infection, including death of mother or fetus, especially if chronic comorbid medical conditions such as diabetes mellitus are present.Case presentationA 36 years old Caucasian pregnant woman with type 1 diabetes underwent mechanical ventilation in gestation week 27 for severe respiratory failure due to influenza and pneumonia. For three weeks during and following her most severe illness, fetal growth could not be detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…suggested that delivery is indicated during the third trimester of pregnancy or in case of deteriorating maternal conditions [23] . Other authors caution against routine delivery, emphasizing that the risks associated with labor or cesarean delivery may be unacceptably high [24] [25] . Cesarean section did not seem to worsen maternal conditions, because intensive management for maternal hypoxia, including ECMO, also led to better than expected outcomes when compared with the usual 30–35% mortality rate reported for ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that delivery is indicated during the third trimester of pregnancy or in case of deteriorating maternal conditions [23] . Other authors caution against routine delivery, emphasizing that the risks associated with labor or cesarean delivery may be unacceptably high [24] [25] . Cesarean section did not seem to worsen maternal conditions, because intensive management for maternal hypoxia, including ECMO, also led to better than expected outcomes when compared with the usual 30–35% mortality rate reported for ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Varios autores han sugerido que mientras se pueda se debe dar manejo para la falla ventilatoria en la embarazada con Ventilación Mecánica No Invasiva (VMNI) para evitar la intubación. Dentro de los parámetros recomendados se encuentran varios como el uso de interfase nasal en modo presión positiva continua en la vía aérea de 8 CmH20, Fracción Inspirada de Oxígeno (FiO2) que garantice una saturación de oxígeno mayor a 90%, presión de soporte de 10 cm H2O (Rojas, Miranda, Ramos, & Fernández, 2011), (Madsen, Strange, Hedegaard, Mathiesen, & Damm, 2013). Del mismo modo, se reportaron casos donde se apoyan con ventilación no invasiva, con soporte de presión inspiratoria de 12 cm H2O, PEEP de 8 CmH2O y Fio2 de 100%, se evidencio, que esta ventilación fue más cómoda y la saturación de oxígeno mejoró en las gestantes (Allerd, Esquinas, Caronica, Mahdavi, & Mina, 2014), (Melians, 2014).…”
Section: Intervención Fisioterapéutica Mediante Técnicas No Invasivasunclassified
“…Con relación a otro tipo de intervenciones, se identificó que el uso de bloqueo neuromuscular (NMB) en el entorno de cuidados críticos, mejora la ventilación y oxigenación en pacientes con SDRA (Ender & Valermann, 2016). También, se habla sobre un soporte de vida extracorpórea, conocido como Oxigenación por Membrana Extra Corpórea (ECMO), la cual ha sido utilizada como una modalidad en el tratamiento del SDRA, permitiendo la oxigenación a través de la intervención vena-vena con la utilización de cánulas (Madsen, Strange, Hedegaard, Mathiesen, & Damm, 2013), (Duarte, 2014).…”
Section: Intervención Fisioterapéutica Mediante Técnicas No Invasivasunclassified
“…), ECMO is a device which allows recovery from the underlying disease while supporting lung function and maintaining safe levels of oxygenation and controlled respiratory acidosis under protective mechanical ventilation settings. According to the literature, ECMO has been successfully used in ARDS due to H1N1 for pregnant women 3,4 and human immunodeficiency virus-infected man, 5 due to cardiopulmonary arrest from pulmonary embolism (PE) and amniotic fluid embolus for the women immediately post-partum, 6 primary graft dysfunction after lung transplantation 7 and lung trauma. 8 We describe the case of young woman post-partum who experienced a group of serious life-threatening complications (DIC, septic shock with cardiopulmonary insufficiency, ARDS, several massive bleeding episodes and massive blood transfusions) and was successfully treated with ECMO, massive blood transfusions and antibiotics.…”
Section: Introductionmentioning
confidence: 99%